The Effect of ESG Score on Financial Performance Mediated by SDG Disclosures in Indonesian Listed Companies 2021-2023 - Shela Sasmitha; Susi Sarumpaet (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study examines the mediating role of SDG disclosure in the relationship between ESG score and financial performance within the mandatory reporting context of non-financial firms listed on the Indonesia Stock Exchange during 2021-2023. Using a purposive sample of 59 companies (177 observations), the analysis employs panel data regression and the Sobel test to evaluate ESG metrics from Refinitiv Eikon alongside disclosure and financial data from corporate reports. Empirical results show that ESG score does not significantly predict SDG disclosure nor directly affect financial performance measured by ROE. Furthermore, SDG disclosure shows no significant association with financial performance and fails to mediate the ESG-ROE relationship. Firm size is the only variable positively related to SDG disclosure, suggesting that reporting practices are more strongly driven by organizational resources and public visibility than by substantive ESG performance. Overall, the findings reveal a decoupling phenomenon, where sustainability reporting in Indonesia tends to reflect symbolic compliance rather than value-creating integration. The study concludes that a credibility gap exists in the capital market, as SDG disclosure has not yet functioned as an effective mechanism for converting ESG performance into financial gains. This study provides evidence on the limitations of SDG disclosure as a value transmission mechanism in emerging market, offering insights for regulators and market participants seeking to enhance the economic relevance and credibility of SDG reporting.